Travers, John (audio interview #1 of 1) - Travers, John; Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - John Travers was interviewed in an office in the Signal Hill City Yard. TOPICS - family background; Japanese families; 1933 Long Beach earthquake; Kid Mexico; WWII; military; municipal employment; and Fiesta de Oro Negro;municipal employment; family background; sports; and Signal Hill Water Department; 6/27/1989